Síntese e análise estrutural de clusters derivados de Hg(EPh)2 (E = Se, Te) - Tirloni, Bárbara (2009)
This work presents a study related to the synthesis and structural analysis of clusters derivative from Hg(EPh)2 (E = Se, Te). Bis(phenylchalcogenide)mercury was used as starting material, which is considered a building block of the synthesized clusters, besides mercury halides and co-ligands. The compounds that were synthesized are: [Hg5(TePh)6(Ph3P)2Cl4] · 2thf (1), [Hg6(TePh)8(py)2Cl4] · py (2), [Hg4(SePh)7Cl(py)]n (3) e [Hg4(SePh)7I(dmf)]n (4). A structural study in the solid state of these compounds was made, and as a tool the X-ray diffraction in single crystal was used. All compounds were characterized by elementar analysis, infrared spectroscopy, thermogravimetric analysis, Raman spectroscopy, gas chromatography mass spectroscopy, energy dispersive Xray spectroscopy and scanning electron microscope.